The Late Cretaceous chondrichthyan fauna of the Elbtal Group (Saxony, Germany) - Fischer, Jan; Kogan, Ilja; Popov, Evgeny; Janetschke, Nadine; Licht, Martin (Food Agricultural Sciences and Technology, 2017)
Upper Cretaceous (upper Cenomanian–lower Coniacian) marine strata of Saxony, eastern Germany, are mainly known for their rich invertebrate fauna, but have also yielded various vertebrate remains. The Saxonian Cretaceous marine strata, predominantly sand- and calcareous siltstones, marls and marly limestones, are mainly restricted to the clastic units of the so-called Elbtal Group, exposed in the area between Meißen and the Czech border in eastern Saxony. The ichthyofauna of the Elbtal Group is quite diverse. Currently, 19 species of cartilaginous fishes have been distinguished. The fauna was clearly dominated by mid- to large-sized lamniform sharks